Is psychosocial risk prevention possible? Deconstructing common presumptions - Leka, Stavroula; Van Wassenhove, Wim; Jain, Aditya Kailash (Elsevier, 2015)
This paper tackles a much debated and often misunderstood issue in the modern world of work, psychosocial risks. Although the prevalence and impact of psychosocial risks is now widely acknowledged as a priority in health and safety in Europe, there remains resistance by key stakeholders in prioritizing psychosocial risk management both in business and policy making. This paper explores why this is still the case by discussing three presumptions in relation to the current state of the art in this area. It examines the validity of these presumptions by summarizing key evidence, policies and practices. It is concluded that, although guidance on psychosocial risks and their management exists in abundance as does evidence to support the ‘case’ for psychosocial risk management, the concept of psychosocial risk is still not clearly understood in its entirety with discussions being focused on negative impacts and not opportunities that can be capitalized upon through effective psychosocial risk management at the organizational and societal levels. A key issue is the false distinction often made between psychosocial factors and issues pertaining to work organization, since psychosocial risks are embedded in certain forms of work organization. The suitability of available methods and tools is also considered as well as existing capabilities in the context of socioeconomic changes and constraints. On the basis of the current state of the art, an action plan for the prevention of psychosocial risks in the workplace is proposed, linked to sustainability and a value-based perspective.